2011
DOI: 10.1302/0301-620x.93b9.27193
|View full text |Cite
|
Sign up to set email alerts
|

A systematic survey of the quality of research reporting in general orthopaedic journals

Abstract: The poor reporting and use of statistical methods in orthopaedic papers has been widely discussed by both clinicians and statisticians. A detailed review of research published in general orthopaedic journals was undertaken to assess the quality of experimental design, statistical analysis and reporting. A representative sample of 100 papers was assessed for compliance to CONSORT and STROBE guidelines and the quality of the statistical reporting was assessed using a validated questionnaire. Overall compliance w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
47
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(54 citation statements)
references
References 24 publications
5
47
0
Order By: Relevance
“…Inter-item variability appears globally consistent across other specialties. [20][21][22][23][24][25]28 In our study, over 90% of RCTs adequately reported scientific background and explaining rationale (item 2), reporting objectives or hypotheses (item 5), and interpreting results in the context of current evidence (item 22). This might be considered unsurprising, as these items represent the better recognised and readily achievable standards in the reporting of RCTs.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…Inter-item variability appears globally consistent across other specialties. [20][21][22][23][24][25]28 In our study, over 90% of RCTs adequately reported scientific background and explaining rationale (item 2), reporting objectives or hypotheses (item 5), and interpreting results in the context of current evidence (item 22). This might be considered unsurprising, as these items represent the better recognised and readily achievable standards in the reporting of RCTs.…”
Section: Discussionmentioning
confidence: 67%
“…Despite this, the mean score was only 8. Suboptimal compliance of RCT reporting to CONSORT is also found across many other surgical specialties including urological surgery, 20 general surgery, 21 neurosurgery, 22 orthopaedic surgery, 23 plastic surgery, 24 and vascular surgery, 20 as well as medical specialties such as cardiology. 25 The deficiencies identified in previous studies include particularly poor reporting of randomisation implementation, masking status, and healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have highlighted widespread weaknesses in published orthopaedic research [23][24][25]. Parsons et al recently noted poor compliance to published guidance for the reporting of clinical research (CONSORT and STROBE) and a general lack of statistical rigour in orthopaedic research [24].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have highlighted widespread weaknesses in published orthopaedic research [23][24][25]. Parsons et al recently noted poor compliance to published guidance for the reporting of clinical research (CONSORT and STROBE) and a general lack of statistical rigour in orthopaedic research [24]. Okike et al showed that studies with a high level of evidence, large sample size, representation from multiple institutions and conflict of interest disclosure are associated with higher citation rates, on which IF depends [26].…”
Section: Discussionmentioning
confidence: 99%